The influence of structural and charge transport properties of PEDOT:PSS layers on the photovoltaic properties of polymer solar cells. (21st September 2020) - Aimukhanov, A.K.; Rozhkova, X.S.; Ilyassov, B.R.; Zeinidenov, A.K.; Nuraje, N.
Abstract : In this study, the effect of modification of poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) morphology on its optical, charge transport, and photovoltaic properties of organic solar cells based on the P3HT:PC60BM bulk heterojunction is presented. It is shown that the addition of isopropyl alcohol to the PEDOT:PSS polymer solution and annealing of spin‐coated PEDOT:PSS film leads to a change in its morphology, charge transport, and optical properties. By an impedance spectroscopy technique, the charge transport properties of PEDOT:PSS films were studied. It was established that the efficiency of carrier transport and the efficiency of the polymer solar cells depends on the structural features of PEDOT:PSS.